Effect of the ligand framework of cobalt clathrochelates on hydrogen evolution electrocatalysis: electrochemical, spectroscopic and Density Functional Theory analyses. (10th August 2017) - Antuch, Manuel; Ranjbari, Alireza; Grigoriev, Sergey A.; Al-Cheikh, Joumada; Villagrá, Angel; Assaud, Loïc; Voloshin, Yan Z.; Millet, Pierre
Graphical abstract: Abstract: Water electrolysis in acidic media requires electrocatalysts that are chemically stable at low pH, such as platinum group metals (PGM). Due to the scarcity and cost of these PGMs, there is a need to find alternatives. Molecular complexes of 3d metals such as cobalt, nickel and iron are potential candidates. Cage metal complexes such as their tris-dioximate clathrochelates have already demonstrated an interesting electrochemical activity, in particular with regard to the hydrogen evolution reaction (HER). In this work, we report the characterization of three different cobalt clathrochelates and discuss their individual activity and performance with regard to the HER. Our objective is to unravel the effect of different peripheric substituents in the caging ligands and to discuss their role in the observed electrocatalytic activities. Theoretical (DFT) and spectroscopic (EPR and XPS) techniques were employed to assess the electronic structure of the different catalysts, which was subsequently coupled to the results obtained by cyclic voltammetry. The electrochemical kinetics of the systems was determined by Nicholson's method. In all cases, the standard rate constant presented values circa 10 −3 cm/s, characteristic of quasi-reversible electron transfers. Thus, the differences in electrocatalytic activities were not due to dissimilarities in the ET kinetics among the molecules. The electroactivity towards the HER was determined by additions of sulfuric acid to the electrochemical cell. The clathrochelate with most strong electron-withdrawing groups presented the lowest overpotential for the HER.